Current and potential pharmacological treatment options for maintenance therapy in opioid-dependent individuals. - Tetrault, Jeanette M; Fiellin, David A (Drugs, 2012)
Opioid dependence, manifesting as addiction to heroin and pharmaceutical opioids is increasing. Internationally, there are an estimated 15.6 million illicit opioid users. The global economic burden of opioid dependence is profound both in terms of HIV and hepatitis C virus transmission, direct healthcare costs, and indirectly through criminal activity, absenteeism and lost productivity. Opioid agonist medications, such as methadone and buprenorphine, that stabilize neuronal systems and provide narcotic blockade are the most effective treatments. Prolonged provision of these medications, defined as maintenance treatment, typically produces improved outcomes when compared with short-duration tapers and withdrawal. The benefits of opioid agonist maintenance include decreased illicit drug use, improved retention in treatment, decreased HIV risk behaviours and decreased criminal behaviour. While regulations vary by country, these medications are becoming increasingly available internationally, especially in regions experiencing rapid transmission of HIV due to injection drug use. In this review, we describe the rationale for maintenance treatment of opioid dependence, discuss emerging uses of opioid antagonists such as naltrexone and sustained-release formulations of naltrexone and buprenorphine, and provide a description of the experimental therapies.
Keywords: Analgesics, Opioid; Humans; Narcotic Antagonists; Opiate Substitution Treatment; Opioid-Related Disorders